Comparative anatomical analyses of the forearm muscles of Cebus libidinosus (Rylands et al. 2000): manipulatory behavior and tool use - Aversi-Ferreira, Tales Alexandre (2011)
The present study describes the flexor and extensor muscles in Cebus libidinosus' forearm and compares them with those from humans, chimpanzees and baboons. The data is presented in quantitative anatomical indices for similarity. The capuchin forearm muscles showed important similarities with chimpanzees and humans, particularly those that act on thumb motion and allow certain degree of independence from other hand structures, even though their configuration does not enable a true opposable thumb. The characteristics of Cebus' forearm muscles corroborate the evolutionary convergence towards an adaptive behavior (tool use) between Cebus genus and apes.